The development of mobile augmented reality for laptop maintenance (MAR4LM) - A. Shaaban, Ousama; Che Mat, Ruzinoor; Mahayudin, Mohd Hafiz (Penerbit UTM Press, 2015)
Currently, laptops have become a necessity to most of the people as laptop provides mobility and helps in doing the task that a normal desktop PC can do.However, the malfunction of the laptop hardware will distract the user work and decrease the productivity.By utilizing Augmented Reality (AR) that combine real world and virtual world, a laptop maintenance application can be made in reality.The objective of this paper is to discuss on how to develop Mobile Augmented Reality for Laptop Maintenance (MAR4LM) applications.This AR application specifically develop for smart phones based on the android platform.Therefore, this study presents a way to understand and discuss the process of using this new technology on the android platforms.This application has been proven in increasing the understanding of the users about their laptop and doing maintenance on their own self.In addition, laptop maintenance tasks will become straightforward, easy to use, interactive, and easily available anywhere and anytime.